One for all and all for one: phenotype assortment and reproductive success in masculinized females. (28th August 2021) - Correa, Loreto A; León, Cecilia; Ramírez-Estrada, Juan; Ly-Prieto, Álvaro; Abades, Sebastián; Hayes, Loren D; Soto-Gamboa, Mauricio; Ebensperger, Luis A
Abstract: Homophily by morphological and behavioral traits has been described in several species of vertebrates, but its functional consequences remain poorly studied. Homophily by plurally breeding females may improve direct fitness by enhancing reproductive success. Female mammals may exhibit phenotypical masculinization due to exposure to androgens during early development, a condition that is associated with maternal performance during subsequent breeding. Our goal was to assess whether female composition (in terms of masculinization) of plurally breeding groups influences female fitness in a natural population of degus (Octodon degus). We assessed if plurally breeding female degus assort themselves by anogenital distance (AGD), an accurate measure of masculinization level. We also quantified if homophily by AGD phenotype affects female reproductive success and the reproductive output of the group. Plurally breeding groups typically included similarly masculinized (i.e., long AGD) females or similarly feminized (short AGD) females, indicating a strong degree of homophily. Females weaned more offspring in plurally breeding groups with more masculinized females. Additionally, standardized variance in the number of offspring weaned decreased in plurally breeding groups with mostly masculinized females, indicating greater reproductive equality in these groups. We conclude that female degus organize into homophilic social groups of similar AGD, and that social groups of masculinized females exhibit a higher reproductive success. Abstract : In mammal species in which mothers produce litters, female pups are exposed to testosterone from male siblings. Testosterone masculinizes the phenotype of female pups during prenatal development. Thus, natural populations of degus are composed of females with different level of masculinization, which become established within different social groups depending on their phenotypes. Masculinized females, and masculinized social groups, wean more pups, because masculinized females share breeding in a more equitable way, cooperating with each other.